2014
DOI: 10.1088/0954-3899/41/4/044002
|View full text |Cite
|
Sign up to set email alerts
|

Diverse, massive-star-associated sources for elements heavier than Fe and the roles of neutrinos

Abstract: Abstract. Massive-star-associated models for production of elements heavier than Fe are reviewed. The important roles of neutrinos in many of these models are discussed along with uncertainties in the relevant neutrino physics. Data on elemental abundances in metal-poor stars are presented and their constraints on diverse sources for elements heavier than Fe are emphasized.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 96 publications
(240 reference statements)
0
10
0
Order By: Relevance
“…This observation demonstrates that mergers of two neutron stars or a neutron star and a black hole are important sites for the r-process (see e.g., Freiburghaus et al 1999b;Goriely et al 2011;Korobkin et al 2012). Other sites (see e.g., Woosley & Hoffman 1992;Banerjee et al 2011;Nishimura et al 2015) associated with core-collapse supernovae (CCSNe) from massive stars have also been proposed and may play an important role in r-process enrichment at the earliest epochs (see e.g., Qian & Wasserburg 2007;Qian 2014;Hansen et al 2014).…”
Section: Introductionmentioning
confidence: 81%
“…This observation demonstrates that mergers of two neutron stars or a neutron star and a black hole are important sites for the r-process (see e.g., Freiburghaus et al 1999b;Goriely et al 2011;Korobkin et al 2012). Other sites (see e.g., Woosley & Hoffman 1992;Banerjee et al 2011;Nishimura et al 2015) associated with core-collapse supernovae (CCSNe) from massive stars have also been proposed and may play an important role in r-process enrichment at the earliest epochs (see e.g., Qian & Wasserburg 2007;Qian 2014;Hansen et al 2014).…”
Section: Introductionmentioning
confidence: 81%
“…is essential not only for studying nuclear structure far from stability, but also accurate mass values are the main nuclear inputs for the rapid neutron-capture process (r process) [7][8][9] which produces around half of the elements heavier than iron. Sensitivity studies [10] have shown that the neutroncapture rates 67 Fe(n, γ ) 68 Fe and 68 Co(n, γ ) 69 Co have a particularly strong impact on the calculated abundances in the weak r process, which produces lighter r-process elements most likely at several astrophysical sites [11][12][13][14][15][16]. These rates, and, in particular, their inverse photodissociation rates depend sensitively on the reaction Q value, i.e., on nuclear masses.…”
mentioning
confidence: 99%
“…Since the pioneer studies of Burbidge et al (1957) and Cameron (1957), there has been a large number of studies in the literature focusing on the astrophysical site(s) of the rapid neutron capture (r )-process. However, the problem has not been solved, but some promising mechanisms were proposed: (i) the innermost ejecta of regular core-collapse supernovae (e.g., Farouqi et al, 2010), (ii) outer layers of supernova explosions (e.g., Qian, 2014), (iii) magneto-rotational jet-driven supernovae (e.g., Obergaulinger et al, 2018), and (iv) neutron stars (NSs) mergers (e.g., Thielemann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%